(untitled) (Fiep Bulletin - online, 2013)
The cerebellar ataxia due to a Cerebral Palsy (CP) is a rare clinical condition, was initially characterized by hypotonic, and little by little, there are changes in the balance and, less commonly, coordination. Objective: This study aimed identify postural changes before and after the procedure therapeutic facilitatório in a child with cerebellar ataxia PC Methodology: Subject: A child under 5 years of age diagnosed with ataxic CP cerebelar.Protocolo of assessment / reassessment: Software Program SAPO. Physiotherapy intervention: Intervention Facilitator: Results: Rating: Asymmetry of the frontal plane: 7, 7% asymmetry sagittal plane: 60,6% projection of the CG’s position on the average position of the ankle (frontal plane): 2,6% position of projection CG on the average position of the ankle (the side): 14.5%. Reassessment: Asymmetry of the frontal plane: - 2,7% asymmetry sagittal plane: 18, 6% projection of the CG’s position on the average position of the ankle (frontal plane): - 0.8% projection of the CG’s position on the average position the ankle (the side): 6,8%.